2020
DOI: 10.1080/15548627.2020.1717129
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition blunts PDGFRA adipose progenitors’ cell-autonomous fibrogenic response to high-fat diet

Abstract: Adipose tissue (AT) fibrosis in obesity compromises adipocyte functions and responses to intervention induced-weight loss. It is driven by AT progenitors with dual fibro/adipogenic potential, but pro-fibrogenic pathways activated in obesity remain to be deciphered. To investigate the role of macroautophagy/autophagy in AT fibrogenesis, we used Pdgfra-Cre Ert2 transgenic mice to create conditional deletion of Atg7 alleles in AT progenitor cells (Atg7 cKO) and examined sex-dependent, depotspecific AT remodeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Body composition was analyzed by nuclear magnetic resonance (Bruker Mouse Minispec, LF90). Blood and fat pads (gonadal (OvAT-EpiAT), subcutaneous (ScAT), brown adipose tissue (BAT)) were frozen in liquid nitrogen or fixed with Formalin (Sigma Aldrich, HT501128), or incubated with collagenase as described (11). Oral glucose tolerance test (OGTT) started by gavage with 2.0 g/kg glucose in mice fasted for 6h.…”
Section: Methodsmentioning
confidence: 99%
“…Body composition was analyzed by nuclear magnetic resonance (Bruker Mouse Minispec, LF90). Blood and fat pads (gonadal (OvAT-EpiAT), subcutaneous (ScAT), brown adipose tissue (BAT)) were frozen in liquid nitrogen or fixed with Formalin (Sigma Aldrich, HT501128), or incubated with collagenase as described (11). Oral glucose tolerance test (OGTT) started by gavage with 2.0 g/kg glucose in mice fasted for 6h.…”
Section: Methodsmentioning
confidence: 99%
“…If adipogenesis was viewed as a mechanism for the healthy expansion of WAT, Atg- knockout mice with favorable metabolic profiles appear contradictory. These findings indicated that Atg5 or Atg7 deletion in mice enhanced oxidation during metabolic activity and reduced browning and fibrosis in WAT ( 65 , 66 , 71 ). The capacity of increased heat production and oxygen consumption may help to explain animals remaining in an insulin-sensitive state, even when WAT adipogenesis is decreased.…”
Section: Obesity and Autophagymentioning
confidence: 87%
“…The transcriptional landscape of TGF-β/BMP family can be regulated by the progenitor in a cell autonomous dependent manner [110], as shown in mice harboring autophagy deficient progenitors. In these mice, the emergence of beige adipocyte features in the white fat depot was coincident with lower fibrosis expression (110).…”
Section: Interplay Between Beige Adipogenic and Fibrogenic Pathwaysmentioning
confidence: 99%
“…Most interestingly, adding BMP in a profibrotic environmental promotes the resolution of fibrosis driving myofibroblast dedifferentiation to regenerate the adipocyte pool [109]. The transcriptional landscape of TGF-β/BMP family can be regulated by the progenitor in a cell autonomous dependent manner [110], as shown in mice harboring autophagy deficient progenitors. In these mice, the emergence of beige adipocyte features in the white fat depot was coincident with lower fibrosis expression (110).…”
Section: Interplay Between Beige Adipogenic and Fibrogenic Pathwaysmentioning
confidence: 99%